Modeling Nurse Job Satisfaction Mediated Remuneration Supported Career Development and Transformational Leadership - Nelli Roza (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Objective: The objective of this study is to examine and create a model that proposes that views of compensation, in conjunction with career development and transformational leadership, operate as a mediating factor in nurse job satisfaction. Methodology: 200 clinical nurses participated in the survey-based study, which was carried out at the Embung Fatimah Regional General Hospital in Batam City. Stratified random sampling was used for the sampling process. The structural model’s results show that career development has a favorable and considerable impact on job satisfaction, which is higher than the effects of transformational leadership and compensation. Greater than the impact of transformational leadership on compensation is the direct and substantial influence of career development on compensation. There is an indirect influence of career development on job satisfaction through remuneration that is greater than the influence of transformational leadership on job satisfaction through remuneration. Conclusion: Since compensation is a mediating variable, our research introduces it. It is imperative for nurses to prioritize their professional career development and adhere to existing legislation when it comes to remuneration management in order to enhance job satisfaction.